Varicella pneumonia in immunocompetent adults: report of two cases, with emphasis on high-resolution computed tomography findings - Gasparetto,Emerson L. (2005)
We report two cases of varicella pneumonia in immunocompetent patients, with emphasis on high-resolution computer tomography manifestations. The predominant findings consisted of multiple bilateral nodules, ranging from 1-10 mm in diameter, with or without a surrounding halo of ground-glass attenuation. Other findings include ground-glass opacities, focal areas of consolidation and small pleural effusions.